Comparing stakeholder participation in Community-Based Tourism (CBT), examples from Thailand - Witchayakawin, Pakin; Abdul Aziz, Yuhanis; Bali Mahomed, Anuar Shah; Abdullah, Nawal Hanim (University of Oradea, Romania, 2022)
The purpose of this qualitative research program was to study and compare stakeholder participation in communitybased tourism (CBT) in communities in Phitsanulok Province and Sukhothai Province in Thailand, using case studies. Data were collected from 35 key informants from 9 villages, selected by purposive sampling, and using a structured interview form as a research tool in face-to-face, in-depth interviews. The program was undertaken during July 2021. Issues identified in an analysis of the data collected were grouped and coded. A number of different issues were identified between CBT communities. A high level of participation in CBT by leaders, homestay owners, and CBT operators was observed. Citizen control level of participation was found in both provinces, but consultation as a participation strategy was found only in Sukhothai Province. As well, differences in participation activities were identified between older participants and young participants and also between the two provinces. Volunteer work attitude and participation by visitors were also differences identified between these two provinces, indicating the different types of tourism, such as develop gastronomic tourism and creative tourism products, that should be offered by CBT communities in the two provinces.